Critical factors for benefits realisation in collaborative university-industry R&D programs. (6th March 2020) - Fernandes, Gabriela; Araújo, Madalena; Andrade, Rita; Pinto, Eduardo B.; Tereso, Anabela; Machado, Ricardo J.
This study aims to help academics and practitioners to realise the benefits resulting from collaborative university-industry research and development (R&D), by identifying the most critical factors for benefits' realisation. A literature review was conducted allowing us to compile a list of 33 most acknowledged benefits resulting from university-industry R&D collaborations, and a list of 66 critical factors for the realisation of the most acknowledged benefits identified. A benefit breakdown structure and a critical factors breakdown structure were developed to provide a better description of the 'variables' that are involved in managing benefits. A two-stage Delphi survey method, involving data analysis from seven invited experts, was conducted to identify the critical factors that should be leveraged in order to realise the most acknowledged benefits from collaborative university-industry R&D. The most common types of critical factors that contribute to benefits realisation in general are: 'strategic', 'inter-relational' and 'cultural'.